Advances in economics and econometrics : theory and applications, ninth World Congress. vol 1 - Econometric Society. World Congress. 2005 : London, England); Blundell, Richard; Newey, Whitney K.; Persson, Torsten (Cambridge : Cambridge University Press, 2006)
This is the first of three volumes containing edited versions of papers and a commentary presented at invited symposium sessions of the Ninth World Congress of the Econometric Society, held in London in August 2005. The papers summarise and interpret key developments, and they discuss future directions for a wide variety of topics in economics and econometrics. The papers cover both theory and applications. Written by leading specialists in their fields, these volumes provide a unique survey of progress in the discipline.
1. The economics of social networks -- 2. Multi-contracting mechanism design -- 3. Allocative and informational externalities in auctions and related mechanisms -- 4. The economics of relationships -- 5. Information in mechanism design -- 6. Communication in economic mechanisms -- 7. Advances in dynamic optimal taxation -- 8. Quantitative macroeconomic models with heterogeneous agents -- 9. Modeling inefficient institutions -- 10. Whither political economy? Theories, facts, and issues -- 11. Comments on Acemoglu and Merlo.
Edited versions of papers and a commentary presented at invited symposium sessions of the ninth World Congress of the Econometric Society, held in London in 2005.
Includes bibliographical references and index.
1
Keywords: Econometrics -- Congresses; Economics -- Congresses